2011
DOI: 10.1557/jmr.2011.360
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbon impurities on lightly doped MOCVD GaN Schottky diodes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…In light of all these results, it is important to consider again the experimental findings of Tompkins and coworkers. 25 In Ref. 25, the authors posit the presence of an unknown forms of carbon in their GaN sample in addition to acceptor type C 1− N .…”
Section: Formmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of all these results, it is important to consider again the experimental findings of Tompkins and coworkers. 25 In Ref. 25, the authors posit the presence of an unknown forms of carbon in their GaN sample in addition to acceptor type C 1− N .…”
Section: Formmentioning
confidence: 99%
“…25 In Ref. 25, the authors posit the presence of an unknown forms of carbon in their GaN sample in addition to acceptor type C 1− N . Our results indicate that the neutral Si Ga − C N complex is a likely candidate for this unknown form of carbon in GaN.…”
Section: Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the C could also have been compensated by H. Some have suggested that C preferentially precipitates out at dislocations, and that higher quality material contains less C (22), but this is the opposite to what we found in that the material with the largest dislocation concentration had the least amount of C. This could be due to the fact that we grew our films at 500 Torr., which is higher than the pressure usually used because the growth rate is slower. Less C is incorporated in MOCVD grown films when they are grown at higher pressures (23,24). We found that the MOCVD UID films grown in four separate labs at 100 Torr.…”
Section: Experimental Procedures and Resultsmentioning
confidence: 80%
“…Several studies of MOCVD GaN homoepitaxy have shown low carbon concentrations at mid‐ to low‐10 15 cm −3 according to secondary ion mass spectroscopy (SIMS). [ 24–27 ] Despite tremendous efforts on suppressing C incorporation by tuning growth conditions, such as V/III ratio, growth temperature, and growth pressure, [ 22,24,28–30 ] lowering C concentration while maintaining a fast growth rate remains challenging.…”
Section: Introductionmentioning
confidence: 99%